Analysis Of Predisposing Factors Affecting Exclusive Breastfeeding On Working Mothers In Pekanbaru City - Rahmawati, Dessy Mustika (Genius Midwifery Journal, 2025)
Introduction: Working mothers play a significant role in decreasing the rate of exclusive breastfeeding in both developed and developing countries. Several factors that can obstruct exclusive breastfeeding for working mothers consist of predisposing factors (knowledge, age, parity. Exclusive breastfeeding provides essential nutrients and health benefits for infants, yet many working mothers face challenges in maintaining this practice due to various factors, including workplace conditions, lack of breastfeeding support, and limited knowledge. Understanding the influence of predisposing factors on exclusive breastfeeding is crucial for developing effective interventions and policies to support working mothers in achieving optimal breastfeeding practices. The aim of this study is to examine the influence of predisposing factors on exclusive breastfeeding practices among working mothers. Method: This research is case-control design. There are 84 samples withcosecutive sampling technique that meet the inclusion criteria, namely mothers who have babies aged 6-12 months who work as State Civil. Data collection methods used questionnaires. Result: Analysis shows that knowledge (p=0.001), affected exclusive breastfeeding for working mothers (p<0.050), and there was no effect of age (p=1,000) and parity (p=0.662). Conslussion: This study concludes that knowledge significantly influences exclusive breastfeeding practices among working mothers, while age and parity do not have a significant effect.